Water for the environment : from policy and science to implementation and management - Horne, Avril C. (Academic Press is an imprint of Elsevier, 2017)
'Water for the Environment: From Policy and Science to Implementation and Management' provides a holistic view of environmental water management, offering clear links across disciplines that allow water managers to face mounting challenges. The book highlights current challenges and potential solutions, helping define the future direction for environmental water management. In addition, it includes a significant review of current literature and state of knowledge, providing a one-stop resource for environmental water managers. Key Features: Presents a multidisciplinary approach that allows water managers to make connections across related disciplines, such as hydrology, ecology, law, and economics; Links science to practice for environmental flow researchers and those that implement and manage environmental water on a daily basis; Includes case studies to demonstrate key points and address implementation issues. --